(untitled) (Revista de Letras, 2016)
Apresentação da Revista de Letras Vol. 1, número 29 de 2007 CONSELHO EDITORIAL DA REVISTA DE LETRAS Abuêndia Padilha Pinto Universidade Federal de Pernambuco abuendia@elogica.com.br Eneida Leal Cunha Universidade Federal da Bahia eneidalealcunha@uol.com.br leal@ufba.br João Azenha Júnior Universidade de São Paulo azenha@usp.br José Luiz Fiorin Universidade de São Paulo jolufi@uol.com.br Leonor Scliar-Cabral Universidade Federal de Santa Catarina lsc@th.com.br Maria do Socorro Silva de Aragão Universidade Federal do Ceará acaragao@terra.com.br Maria Helena Mira Mateus Universidade de Lisboa mhm@.ip.pt Marcia Arbex Universidade Federal de Minas Gerais marphi@larnet.com.br Roland Walter Universidade Federal de Pernambuco walter_roland@rotmail.com Maria Esther Maciel Universidade Federal de Minas Gerais memaciel@yahoo.com.br Solange Coelho Vereza Universidade Federal Fluminense svereza@uol.com.br